Assessment of competition indices of an unlogged oriental beech mixed stand in Hyrcanian forests, Northern Iran - MOJTABA AMIRI; REZA NAGHDI (Society for Indonesian Biodiversity, 2016)
Amiri M, Naghdi R. 2016. Assessment of competition indices of an unlogged oriental beech mixed stand in Hyrcanian forests, Northern Iran. Biodiversitas 17: 306-314. Studying on structural dynamics of natural forest ecosystems is an important subject in closeto-nature silviculture and the pertaining tending operations. The objective of this research was to analyze the competition indices of the tree species and some structural characteristics in an unlogged mixed-beech natural forest stand located in Shastkalate forest, Northern Iran. To do so, the required data was collected from a 16ha (400×400 m2) permanent plot established in 2006. The characteristics of the trees including species, DBH, total height, stem height, crown diameter, and the distance between the stems were measured and recorded. The results indicated that alder and wild service have the highest and lowest DBH, respectively, and also beech species comprises almost half of the basal area as well as the total volume of the stand trees. The results of competition effect on the distribution of the given species tree stems and also on low (≤30 cm), medium (35-50 cm), large (55-70), and very large (>75 cm) diameter classes showed that the competition existing among individual trees decreased as their respective distances, DBH, and crown area enhanced by the increase in distance, such that the highest (R2adj= 0.79) and the lowest (R2adj= 0.38) values of competition indices (e.g. Stand density and Relative Spacing index) were, respectively, observed in ≤30 cm and >75 cm diameter classes. The data of the present research, as well, indicated that a more appropriate competition index can be selected by increasing the number of the variables applied in competition indices such as considering the distance among stems, DBH, crown area, and height. As a whole, in the present study the distance-dependent competition indices (e.g. distance-weighted size ratios and Daniel et al) presented better results.